A mechanical, electrical dual autonomous self-healing multifunctional composite hydrogel. (September 2021) - Wang, Y.; Jia, Y.; Ren, H.; Lao, C.; Peng, W.; Feng, B.; Wang, J.
Abstract: The versatile properties make hydrogels a potential multipurpose material that finds wide applications. However, the preparation of multipurpose hydrogels is very challenging. Here, we report a method based on free radical reaction and composite mechanisms to prepare mechanical and electrical self-healing multifunctional hydrogels. In this study, the introduction of imidazolium salt ionic liquids and glycerol in the hydrogel system endows the gels with good antibacterial, conductive, and adhesive properties and excellent antifreeze properties. The testing results show that the as-prepared hydrogel has stable mechanical and electrical properties even under the extremely cold condition of −50°C after self-healing. Moreover, the active esters formed in the dynamic radical reaction have better reducibility, thus further investing the as-prepared hydrogel with high antioxidant activity. The application results show that these comprehensive properties make such hydrogel system very useful in wound repair and wearable strain sensors. Graphical abstract: Image 1